Study of non-uniform bedding due to voids under jointed PVC water distribution pipes - Balkaya, Muge; Moore, Ian D.; Saglamer, Ahmet (Elsevier BV, 2012)
Abstract In this paper, the stresses and deformations are studied in a buried PVC water pipe with bell-and-spigot joints, and with localized voids leaving the invert and haunches unsupported. The finite element program ABAQUS is used to assess changes in the stresses and deformations as a function of the void geometry under the pipe. The results of the analyses are evaluated in terms of factors of safety and displacements. The minimum factor of safety calculated for the specific pipe and bedding conditions considered in this study decreases by 36% if the void forms away from the joint, and by 30% when a joint is centred over the void. The most critical void location is directly under the bell of the pipe, likely because this permits the greatest rotation at the joint. This is also the most likely void location resulting during construction, since the bedding is generally excavated under protruding bells. In each case being considered, the factor of safety remained above 5, illustrating that current water pipe design includes conservative choice of wall thickness to accommodate imperfections of this kind, in addition to other factors such as pressure surges.